2022
DOI: 10.1111/jipb.13266
|View full text |Cite
|
Sign up to set email alerts
|

Sdr4 dominates pre‐harvest sprouting and facilitates adaptation to local climatic condition in Asian cultivated rice

Abstract: Pre‐harvest sprouting (PHS), which reduces grain yield and quality, is controlled by seed dormancy genes. Because few dormancy‐related genes have been cloned, the genetic basis of seed dormancy in rice (Oryza sativa L.) remains unclear. Here, we performed a genome‐wide association study and linkage mapping to dissect the genetic basis of seed dormancy in rice. Our findings suggest that Seed Dormancy4 (Sdr4), a central modulator of seed dormancy, integrates the abscisic acid and gibberellic acid signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Domestication and improvement are usually characterized by reduced nucleotide diversity (Zhao et al, 2022). To explore this association for OsNCED3 , we compared the nucleotide diversity (π) across their genome regions using 4701 rice germplasm accessions and 451 WILD accessions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Domestication and improvement are usually characterized by reduced nucleotide diversity (Zhao et al, 2022). To explore this association for OsNCED3 , we compared the nucleotide diversity (π) across their genome regions using 4701 rice germplasm accessions and 451 WILD accessions.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that freshly harvested seeds in different rice subpopulations exhibit distinct variations in seed dormancy (Zhao et al, 2022). Japonica subgroups had a higher mean germination rate than the IND subgroup, and AUS had the lowest mean germination rate (Zhao et al, 2022). Natural variation analysis showed that japonica rice varieties (TEJ and TRJ) mainly carried the Taken together, in this study, we made the observation that overexpressing OsNCED3 markedly enhanced PHS resistance, grain size and weight, and suggest that OsNCED3 is a valuable genetic resource for PHS resistance and grain development improvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proper dormancy of seeds can solve the problem of preharvest sprouting, thereby reducing losses and increasing yield. Unfortunately, during domestication, rice seed dormancy was largely lost 23 . Therefore, it is necessary to identify rice varieties that have strong dormancy and clone dormancy genes to improve rice yield.…”
Section: Introductionmentioning
confidence: 99%